2014
DOI: 10.1177/0887302x14556151
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effects of Design and Materials on QuadGard™ Body Armor Systems

Abstract: QuadGard™ arm and leg protection systems were developed to better protect key areas of arms and legs from blast fragments. The purpose of this investigation was to use sweating thermal manikin Walter™ and examine the intrinsic clothing insulation (R cl ), intrinsic clothing evaporative resistance (R ecl ), micro-climate temperature, and moisture retention of three QuadGard™ systems (QG II, QG IV Ventilated, and QG IV Not Ventilated) constructed with two ballistic materials, Dyneema 1 and Kevlar 1 . With simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…For example, runners want their clothing to meet expected performance (Leksrisompong 2010); pear workers want clothing to increase mobility and work efficiency (Choi and Ashdown 2002); golfers want to have sufficient back length to achieve an uninhibited swing (Wheat and Dickson 1999); sailors require uniforms which allow quick actions while the body is in a confined space (Bye and Hakala 2005); and soldiers want body armor to not restrict ease of movement (Starr et al 2015).…”
Section: Current Uniform Attributes and Expected Performance Of New Umentioning
confidence: 99%
See 1 more Smart Citation
“…For example, runners want their clothing to meet expected performance (Leksrisompong 2010); pear workers want clothing to increase mobility and work efficiency (Choi and Ashdown 2002); golfers want to have sufficient back length to achieve an uninhibited swing (Wheat and Dickson 1999); sailors require uniforms which allow quick actions while the body is in a confined space (Bye and Hakala 2005); and soldiers want body armor to not restrict ease of movement (Starr et al 2015).…”
Section: Current Uniform Attributes and Expected Performance Of New Umentioning
confidence: 99%
“…Breathable and permeable uniforms would help practitioners keep a comfortable temperature; however, the non-breathable and non-permeable uniforms may become sticky in sweaty conditions and therefore impede practitioners' mobility. Empirical studies indicated that comfort influenced soldiers' mobility (Starr et al 2015) and it was the most important attribute that affects a runner (Çivitci and Dengin 2014) and male tennis players' performance (Jin and Black 2012).…”
Section: Current Uniform Attributes and Expected Performance Of New Umentioning
confidence: 99%
“…Chen, Fan, and Zhang (2003) used a sweating thermal manikin to determine that clothing insulation decreases by as much as 2-8% as perspiration increases. Quintela, Gaspar, and Borges (2004) analyzed heat exchange using a thermal manikin by varying the chamber temperature between 13 C and 29 C. More recently, a thermal manikin was used to test a prototype shirt with cooling capabilities (O'Hara & Serres, 2013), to examine equestrian body protectors (Dlugosch, Hu, & Chan, 2013), and to test arm and leg blast-fragment protection systems (Starr et al, 2015). This study's purpose was to determine whether gender-related thermoregulatory (sweat pattern) and anthropometric differences impact relative humidity (RH) levels in the microclimate while wearing a unisex ballistic vest, using a thermal manikin for repeatability.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the case of natural fibres, high-performance fibres such as Nomex® and Twaron® are widely used in fire protection and body armour clothing respectively [39]. The heat transfer behaviour of these materials is necessary to be analysed when they are subjected to the intense environment.…”
Section: Introductionmentioning
confidence: 99%